A Novel CAPN1 Mutation Causes a Pure Hereditary Spastic Paraplegia in an Italian Family - Cotti Piccinelli, Stefano; Bassi, Maria T.; Citterio, Andrea; Manganelli, Fiore; Tozza, Stefano; Santorelli, Filippo M.; Gallo Cassarino, Serena; Caria, Filomena; Baldelli, Enrico; Galvagni, Anna; Santoro, Lucio; Padovani, Alessandro; et al. (Frontiers in Neurology, 2019)
CAPN1 encodes calpain-1, a large subunit of μ-calpain, a calcium-activated cysteine protease widely present in the central nervous system. Mutations in CAPN1 have recently been identified in a complicated form of Hereditary Spastic Paraplegia (HSP) with a combination of cerebellar ataxia and corticomotor tract disorder (SPG76). Therefore, CAPN1 is now considered one of those genes that clinically manifest with a spectrum of disorders ranging from spasticity to cerebellar ataxia and represent a link between Spinocerebellar Ataxia and HSP, two groups of diseases previously considered separate but sharing pathophysiological pathways. We here describe clinical and molecular findings of two Italian adult siblings affected with a pure form of HSP and harboring the novel homozygote c.959delA variant (p.Tyr320Leufs*73) in the CAPN1 gene. Although the reason why mutations in CAPN1 may cause heterogeneous clinical pictures remains speculative, our findings confirm that the spectrum of the CAPN1-linked phenotypes includes pure HSP with onset during the third decade of life. Further studies are warrantied in order to clarify the mechanism underlying the differences in CAPN1 mutation clinical expression.